Chemical composition and antimicrobial activity of the essential oils of some species of Anthemis sect. Anthemis (Asteraceae) from Sicily. Issue 23 (2nd December 2017) - Riccobono, Luana; Maggio, Antonella; Bruno, Maurizio; Spadaro, Vivienne; Raimondo, Francesco Maria
Abstract: The chemical composition of the essential oils isolated from the aerial parts of Anthemis arvensis L. subsp. arvensis, Anthemis cretica subsp. messanensis (Brullo) Giardina & Raimondo and from flowers and leaves of Anthemis cretica subsp. columnae (Ten.) Frezén were determinated by GC–FID and GC–MS analyses. Torreyol (85.4%) was recognised as the main constituent of the Anthemis arvensis subsp. arvensis essential oil, while in the essential oils of Anthemis cretica subsp. messanensis, collected on the rock and cultivated in Hortus Botanicus Panormitanus, ( E )-chrysanthenyl acetate (28.8 and 24.2% resp.), 14-hydroxy- α -humulene (8.1 and 5.3% resp.), santolina triene (8 and 5.8% resp.) and α -pinene (6.7 and 5.4% resp.) prevailed. 18-cineole (13.3 and 12.2% resp.), was the main component of both flower and leaf oils of Anthemis cretica subsp. columnae together with δ -cadinene (9.0 and 8.2% resp.) and ( E )-caryophyllene (8.3 and 5.6% resp.). Abstract :